Marketing Industry Class Management in Vocational High Schools - Briliansa Rama Luthfi; Surya Jatmika (South Sulawesi Education Development (SSED), 2024)
The purpose of this study is to describe the management of marketing industry classes, namely planning, implementation, evaluation, and constraints.This research uses a qualitative research approach with a case study research design. The informants of this research consisted of the vice principal of curriculum, head of marketing expertise programme, manager representative, and industry class students. Data analysis used interactive analysis. The results showed that the planning consists of curriculum planning, learner planning, infrastructure planning, and learner planning. The implementation of industrial classes consists of the implementation of learning and the implementation of industrial work practices. Evaluation of industrial classes consists of evaluating learner activities and evaluating the organisation of industrial classes. The conclusion of this study shows the results of industrial class planning, industrial class implementation and industrial class evaluation. But still experiencing obstacles in several ways, including the limitations of schools in providing infrastructure, the lack of orderly attendance of students when doing industrial work practices, and distance problems that result in students having to stay at dormintory.